2005
DOI: 10.1542/peds.2004-1518
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Urinary Matrix Metalloproteinases Parallels the Extent and Activity of Vascular Anomalies

Abstract: Objective. Matrix metalloproteinases (MMPs) and the angiogenic proteins basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF) have been implicated in mechanisms of human cancer and metastasis. Assays were conducted on the urine of patients with vascular anomalies (tumors and malformations), relatively common and occasionally life-threatening disorders for which few therapies exist. We sought to determine whether these angiogenesis modulators are present in the urine and whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 26 publications
3
81
0
7
Order By: Relevance
“…These activities diminish with age and were less common in the age range of subjects investigated for this study (23). Furthermore, urinary MMP activities associated with physiological growth tend to be lower than the activities associated with pathological conditions of vascular remodeling and usually do not contain the high-molecular-weight complexes of NGAL/MMP-9 and MMP-9 multimers (22).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…These activities diminish with age and were less common in the age range of subjects investigated for this study (23). Furthermore, urinary MMP activities associated with physiological growth tend to be lower than the activities associated with pathological conditions of vascular remodeling and usually do not contain the high-molecular-weight complexes of NGAL/MMP-9 and MMP-9 multimers (22).…”
Section: Discussionmentioning
confidence: 79%
“…Even the large 125-kDa complex of MMP-9 and neutrophil gelatinaseassociated lipocalin (NGAL; also known as lipocalin-2), which protects MMP-9 from autodegradation, can be excreted in urine. MMP-2, MMP-9, and NGAL/MMP-9 are nearly absent in urine of unaffected adults but are excreted by individuals with various types of cancer or invasive vascular malformations and have been shown to predict both clinical stage and prognosis (10,11,23). …”
mentioning
confidence: 99%
“…Doxycycline is an antibiotic that heals microcystic and macrocystic lymphatic malformations that are associated with elevated VEGF and MMPs [6,29,39,40]. In bone and soft tissue malignancy cell cultures, doxycycline demonstrates antitumoral properties with inhibition of MMP and angiogenesis [12,13,15], inhibition of osteoclastic function, and induction of osteoclastic apoptosis [12,13,15,19].…”
mentioning
confidence: 99%
“…64 The overexpression of Akt1 in murine endothelial cells resulted in the development of vascular malformations characterized by dysfunctional endothelial cell remodeling. 85 Marler et al 86 showed increased levels of urine MMPs in patients with both vascular tumors and vascular malformations compared to control subjects. An increased expression of urinary MMPs correlated with the extent and activity of the vascular anomalies and may offer a method for monitoring treatment efficacy in patients with vascular malformations.…”
Section: Hemangioendotheliomas Key Point D Antiangiogenic Treatment Hmentioning
confidence: 99%